Effects of aerosol on shallow convective clouds - Spill, G (2021)
Clouds and aerosols are deeply significant components of the Earth's atmosphere and climate system. Yet, aerosol-cloud interactions, particularly for shallow convective clouds, remain poorly understood and highly uncertain. Many varied, and often conflicting, hypotheses of aerosol effects on shallow clouds have been proposed, reflecting the myriad pathways and mechanisms through which they interact. This thesis uses high-resolution, large-domain simulations to investigate the effects of aerosol on shallow convective clouds. Large-domain simulations are performed to capture the large-scale behaviour of the cloud field in response to aerosol perturbations. Increased aerosol is found to lead to decreases in domain-mean precipitation, increases in domain-mean liquid water path, and little impact on cloud fraction or the frequency of higher precipitation rates, in contrast to existing research. It is hypothesised that these differences are due to differing approaches to the model setup. Idealised and realistic simulations of trade wind cumuli are performed, producing starkly different cloud fields and responses to increases in aerosol. The idealised simulations experience significant changes in their thermodynamic evolution along with convective deepening, in contrast with little change in the thermodynamic evolution of the realistic simulations. Detailed investigation of the properties and life-cycle of individual clouds highlights the different responses of clouds with different characteristics to changes in aerosol. Cloud lifetimes are directly quantified using a cloud tracking algorithm, displaying little change in response to increased aerosol. Shallow clouds occur less frequently, while congestus clouds may become deeper. Increased aerosol notably delays the onset of precipitation, and reduces the probability of precipitation. This analysis emphasises the importance of representing the diversity present in realistic trade wind cloud fields.